1994
DOI: 10.1111/j.1439-037x.1994.tb00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weed Removal on Productivity of Chickpea (Cicer arietinum L.) and Lentil (Lens culinaris Med.) in a Mediterranean Environment

Abstract: Three field experiments were conducted on chickpea {Cicer arietinum L.) and four on lentil {Lens culinaris Med.) at different winter-sown rainfed locations in Jordan from 1988/89 to 1990/91 to study the effect of the duration of weed-free and weed-infested conditions on yields and yield components of the crops. Chickpea seed yields were reduced on average by 81 % and straw yields by 63 % when fields remained weed infested until harvest compared with weed-free conditions throughout the growing season. The corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 9 publications
6
29
0
Order By: Relevance
“…Means in the column and rows followed by the same letters are not significantly different at 5% level of significance These results were in line with the previous research conducted by [49] who found that 100 seed weight was increased with reduced weed infestation in mung bean. Similar results were reported on chickpea by [50], [31], [32] and [33] where weed interference decreased simultaneously number of pods plant -1 and 100 seed weight. Further, it was found that except weedy check under all the weeding frequencies, the hundred seed weight was significantly higher at Sirinka than at Jari (Table 7).…”
Section: Hundred Seed Weightsupporting
confidence: 80%
“…Means in the column and rows followed by the same letters are not significantly different at 5% level of significance These results were in line with the previous research conducted by [49] who found that 100 seed weight was increased with reduced weed infestation in mung bean. Similar results were reported on chickpea by [50], [31], [32] and [33] where weed interference decreased simultaneously number of pods plant -1 and 100 seed weight. Further, it was found that except weedy check under all the weeding frequencies, the hundred seed weight was significantly higher at Sirinka than at Jari (Table 7).…”
Section: Hundred Seed Weightsupporting
confidence: 80%
“…Weeds compete with the crop for nutrients, water, and light, reducing crop yields and grain quality (Turk & Tawaha 2003). Yield losses in lentil of 40-80%, as a result of weeds, have been reported (Saxena & Wassimi 1980;Chaudhary & Singh 1987;Al-Thahabi et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Farmers often consider weeds to be the major biological constraint to growing legume crops successfully. In fact, compared with cereals, legume species generally have an open growth habit and a slow growth rate in the early stages of the crop cycle, characteristics that favor the emergence and growth of weeds (Al-Thahabi et al, 1994;Smitchger et al, 2012). Weed interference in dry bean can reduce seed yield as much as 83% (Arnold et al, 1993;Malik et al, 1993;Chikoye et al, 1995) and can interfere with harvest efficiency and may cause staining and reduce seed quality (Burnside et al, 1994;Bauer et al, 1995;Urwin et al, 1996).…”
Section: Introductionmentioning
confidence: 99%